PERANCANGAN ANIMASI 3D DENGAN MENGGUNAKAN TEKNIK STOP MOTION DAN PARTICLE SYSTEM PROGRAM STUDI TEKNIK INFORMATIKA UNIVERSITAS TANJUNGPURA - Wijayanto, Agung (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2014)
Stop motion is one of the traditional animation technique that has been use from the beginning of an early animation film up until now.  As one of the traditional technique, there is a lot of things that can not be animated with stop motion. One of them is a movement of an animation that shape like a particle with abstract and fuzzy movement. Based on that reason, the production of an short animation film is conducted that will combine stop motion technique with particle system; which is a digital animation technique. In this research, particle system technique will be added in post production so the elemental effects that can’t be produce by stop motion technique can be added. Resulting in one animation that combine the traditional animation technique, stop motion, with digital animation technique, particle system. From the qualitative comparative technique that comparing the scene before and after post production state of effects, also quantitative comparative technique with the sum of particle that had been emitted and the pixel count and also velocity count. It is concluded that the particle system technique succeeded in covered the lack  of stop motion technique in animated the movement of an abstract and fuzzy object.